Mengukir Jejak Loyalitas: Studi Tentang Bagaimana Citra Perusahaan Coday Coffee Yogyakarta Membentuk Loyalitas Pelanggan yang Dimediasi Oleh Kepercayaan Dan Kepuasan - Septiana Septiana; Agus Utomo (Excellent, 2026)
One of the most important elements in maintaining the survival and expansion of a company in the face of increasingly fierce competition is customer loyalty. Customer loyalty is characterized by a customer's promise to remain loyal to the business by continuing to make regular purchases in the future, even in the face of competition from similar businesses. This study aims to Carve a Trail of Loyalty: A Study of How Coday Coffee Yogyakarta's Corporate Image Shapes Customer Loyalty Mediated by Trust and Satisfaction. This study uses a quantitative approach with an explanatory research type. Data were collected through a survey using a questionnaire to 192 respondents who are Coday Coffee customers, with a simple random sampling technique. Data analysis was carried out using IBM SPSS version 25 with the help of PROCESS Macro Hayes version 4.2 Model 4. The results showed that corporate image has a positive and significant effect on customer satisfaction (? = 0.3161; p < 0.05), but does not have a significant effect on customer trust (? = 0.0030; p > 0.05) and customer loyalty (? = 0.0814; p > 0.05). Customer satisfaction has a positive and significant effect on customer loyalty (? = 0.5235; p < 0.05), while customer trust has no significant effect on customer loyalty (? = 0.0000; p > 0.05). The results of the mediation test indicate that customer satisfaction significantly mediates the relationship between corporate image and customer loyalty with an indirect effect of 0.1655 and a confidence interval of BootLLCI = 0.0934 to BootULCI = 0.2476, while customer trust does not act as a mediator. These findings indicate that building customer loyalty at Coday Coffee is more effective through enhancing corporate image oriented towards customer satisfaction than through direct customer trust.